Penegakan Hukum terhadap Kejahatan Genosida dalam Perspektif Hukum Pidana Internasional - Vallent Margaretha; Dwi Putri Lestarika (AHKAM, 2026)
The crime of genocide is one of the most serious international crimes because it threatens the survival of human groups and the stability of global peace, as regulated in the 1948 Genocide Convention and strengthened through the existence of the International Criminal Court (ICC) under the 1998 Rome Statute as a permanent judicial institution for prosecuting individual criminal responsibility. This study aimed to analyze the mechanisms of law enforcement against the crime of genocide from the perspective of international criminal law, identify the obstacles encountered, and assess its effectiveness in realizing global justice. This study used a normative legal method with statutory, conceptual, and case approaches through an examination of international legal instruments, expert doctrines, and international judicial practice. The results showed that although the international legal framework is normatively quite comprehensive in regulating the prosecution of genocide, its implementation still faces various obstacles, including the limited jurisdiction of the ICC, which is not yet universal, the application of the principle of complementarity that depends on the willingness of states, and dependence on international cooperation in the law enforcement process. In addition, global political dynamics, including the influence of major powers and the role of the United Nations Security Council, also affect the prosecution process, thereby potentially creating selectivity in law enforcement. Thus, this study confirms the existence of a gap between ideal legal norms and the reality of international criminal law enforcement practice, which affects the effectiveness of handling the crime of genocide and the level of trust of the international community in the global justice system.